Kombinasi Pemberian Suara Relaksasi Alam dan Relaksasi Nafas Dalam Terhadap Tingkat Kecemasan Keluarga Pasien di Ruang ICU RSUD Ulin Banjarmasin - Intriani, Nadia Meilanda; Nasution, Tina Handayani; Herry Setiawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2025)
ABSTRACT Background: The anxiety experienced by the family limited their involvement during the patient's care. The family's inability to be with the patient in the ICU made it difficult for them to provide support and fulfill their responsibilities. A combination of nature relaxation sounds and deep breathing relaxation is one of the non-pharmacological therapies that could help reduce anxiety. Purpose: Understanding the effect of the combination of natural relaxation sounds and deep breathing relaxation on the level of anxiety among families of patients in the waiting room at RSUD'S ICU of Ulin Banjarmasin Methods: With a quasi-experimental pre and post-test design using consecutive sampling technique involving 29 respondent families of patients in the ICU waiting room, the questionnaire utilized the HARS (Hamilton Anxiety Rating Scale). Bivariate analysis employed the Wilcoxon Test to analyze the impact before and after the intervention was administered. Result: In the data analysis, a significance value of 0.000 (p < 0.05) was obtained, with Ha accepted, indicating an influence of the combination of nature relaxation sounds and deep breathing relaxation on the anxiety levels among families of patients in the waiting room at RSUD'S ICU of Ulin Banjarmasin. Conclusion: The decrease in the anxiety levels among families of patients before and after the intervention with nature relaxation sounds and deep breathing went from severe anxiety (63.3%) to mild anxiety (53.3%). The research results indicated that 10 respondents experienced a decrease in scores of more than 10 points. Therefore, this intervention can be utilized. Keywords: Anxiety; Deep Breathing Relaxation, Family, ICU, Nature Relaxation Sounds